PITUITARY APOPLEXY – A RARE CAUSE OF HYPONATREMIA - DR. SAKTHI SELVA KUMAR,; DR.M.V.BHARGAVI,; DR.S.PALANIANDAVAN, (International Journal of Pharma and Bio Sciences, 2016)
Hyponatremia is a very common electrolyte imbalance caused due to many etiologies, but is rarely due to hypopituitarism. A non-functional pituitary macro adenoma usually results in complaints like headaches and/or visual field defects might extend to blindness. But hyponatremia in macro adenoma is rare. Severe hyponatremia is a life-threatening emergency; hence an accurate diagnosis and a prompt initiation therapy are needed. We report a patient presenting with hyponatremia secondary to hypopituitarism along with hypothyroidism due to pituitary macro adenoma.